The Double Node Local Optimizer for Travelling Salesman Problem - Hammad, Azhar Waleed (Al-Nahrain Journal of Science, 2018)
In this paper we introduce a new local optimizer consists of two operations, swap and insert. Our new local optimizer can improve the travelling sales man shortest route problem obtained by metaheuristic algorithms directly and also those routes found by using other local optimizers. To see how well the new local optimizer, it was tested on two problems, the first is a benchmark problem and it is succeeded in reducing the published optimum route, the second problem is handling the problem of finding the shortest route for Arab capitals. Also, the double node local optimizer was used to improve the route obtained by nearest neighborhood method.